The Great Crisis and Fiscal Institutions in Eastern and Central Europe and Central Asia - Barbone, Luca (2012)
This paper examines fiscal outcomes in Eastern and Central European countries before and during the global crisis of 2008-2010. These outcomes are evaluated in the context of overall changes in fiscal institutions and global market conditions. Eastern and Central European countries situations improved dramatically in the pre-crisis period as tax revenues boomed, and fiscal institutions were reformed. Expenditures increased quite significantly in real terms for some of the countries in the pre-crisis era so that when tax revenues collapsed in the wake of the crisis, the countries were left with large deficits. Institutional reform helped countries manage their fiscal situations better, but the crisis also exposed shortcomings of the status quo. In the post-crisis period, fiscal institutions aimed at promoting fiscal discipline are being strengthened. Governments will also need to take a closer look at the sustainability of current expenditure patterns, particularly the strong emphasis on social expenditures.